MynxGrip for Closure of Antegrade Puncture After Peripheral Interventions With Same-Day Discharge. (February 2017) - Pruski, Maciej J.; Blachut, Aleksandra M.; Konkolewska, Magda; Janas, Adam; Hrycek, Eugeniusz; Buszman, Piotr P.; Kiesz, Radoslaw S.
Background: This was the first prospective study to assess the safety and efficiency of MynxGrip vascular closure device (VCD) in peripheral interventions with antegrade access. Methods and Results: We enrolled 66 consecutive patients from 1 center. All patients were discharged home on the day of procedure and were observed for adverse events at 1 and 30 days of follow-up. No major complications were observed. The rate of minor complications (conversion to manual or mechanical compression) was 7.6%. Postdischarge, 3% of patients experienced minor complications—small abscess, ipsilateral deep vein thrombosis. In 1 patient, a second VCD was deployed after device failure. The derived device failure rate was 5.9%. No patients required hospitalization. No late bleeding and no hematomas >6 cm were noted. The mean time to discharge was 4 hours and 5 minutes. Conclusion: The MynxGrip was safe and effective in sealing access sites after antegrade femoral artery puncture with same-day discharge.